2019
DOI: 10.1016/j.ijbiomac.2019.08.184
|View full text |Cite
|
Sign up to set email alerts
|

The endothelial nitric oxide synthase gene G894T, glutathione S-transferase (GSTM1 and GSTT1) polymorphisms as a risk factor in the patient with nephrolithiasis

Abstract: Background The genetic features indicate a crucial role in nephrolithiasis. The present study was aimed to investigate the role of Glutathione-S-transferase Mu (GSTM1), Glutathione-S-transferase Theta (GSTT1) and endothelial nitric oxide synthase (eNOs) gene polymorphism in nephrolithiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…GSTA3 has a protective effect on Tubular epithelial-mesenchymal transition in renal fibrosis ( Xiao et al, 2016 ). Glutathione S transferase M1 (GSTM1) is an important member of phase II toxic metabolizing enzyme GST family, which plays a detoxification role by binding with glutathione ( Mehdi et al, 2019 ). It is reported that GSTM1 can repair acute kidney injury by reducing endoplasmic reticulum and oxidative stress ( Dai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…GSTA3 has a protective effect on Tubular epithelial-mesenchymal transition in renal fibrosis ( Xiao et al, 2016 ). Glutathione S transferase M1 (GSTM1) is an important member of phase II toxic metabolizing enzyme GST family, which plays a detoxification role by binding with glutathione ( Mehdi et al, 2019 ). It is reported that GSTM1 can repair acute kidney injury by reducing endoplasmic reticulum and oxidative stress ( Dai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…23 GSH has many important biological functions 24 and plays an important role in many biochemical processes, including redox activity, 25 signal transduction 26 and gene regulation. 27 Moreover, cell health is critically related to the ratio of reduced glutathione (GSH) to oxidized glutathione (GSSG). 28 For example, the ratio is affected by the conversion of glutathione to oxidized glutathione when oxidative stress occurs.…”
Section: Introductionmentioning
confidence: 99%